KEBERAGAMAN MEDIA KOMUNIKASI, SENI DAN KRIYA - Agus Ahmadi (Institut Seni Indonesia Surakarta, 2006)
Pluralism means that communication media and aft, are having so much variety. wide spread in society and having many different types. Arts are partola branch of communication media called recreation/entertainment media. In human live or society that plurality is seen much than homogeneity or uniformity. Communicating can be said as a language process by having a conversation, Interaction, and information, data and messages, exchanges through media, one of it is recreation media or arts including handicrafts. Beside the material or media used in arts, arts pluralistic can also be seen ;nets function, technique and message inside the ails. Hand/crafts pluralistic can be classified on their raw matenaiS, productions and functrons.Â